Audio feedback in distance design education - Jones, Derek; Hilton, Clive (Design and Technology Education: An International Journal, 2022)
This paper reports on the use of feedback as part of a tuition strategy applied in a distance design course at The Open University in the United Kingdom. A blended feedback model (audio and summary text) was compared to the existing written-only feedback model in terms of student attainment, use, and perception. Comparison of feedback models confirms findings in the literature around the affective and interpersonal qualities of audio feedback, primarily in developing the relationship between student and tutor in a distance design education setting. The blended model demonstrated no major differences in student assessment outcome but differences in student activity and approach to feedback were observed, specifically that students engage in a series of extended and unexpected feedback opportunities beyond simple models of feedback normally assumed. It is proposed that a blended model, as part of a suite of approaches in a learning design, is more effective than either written or audio alone, allowing far richer student-tutor interactions and outcomes in distance settings.